REHABILITATION OF DRUG USERS IN DIGNITY’S JUSTICE PERSPECTIVE - Bambang Setiawan (Jurnal Pembaharuan Hukum, 2018)
Drugs is a dangerous threat for all people, in addition to the transnational, an increase in drug-related crime is fairly significant. Rehabilitation is one of the efforts to combat drugrelated crimes. However, research shows drug rehabilitation policies for drug users normatively still centrally to law enforcement. In practice, law enforcement still do not understand the philosophy of rehabilitation and prone to the Corruption, Collusion and Nepotism. As a way out, dignified Justice concept is offered to drug users for at humanity. Referring to one of the values of Pancasila, namely, democracy permusywaratan practiced in customary justice. Policy toward drug rehabilitation should involve drug users to help determine period in the future.